CUSTOMARY LAND RIGHTS OF ORANG ASLI: A CASE STUDY IN KAMPUNG PARIT GONG, NEGERI SEMBILAN, MALAYSIA (UUM Journal of Legal Studies, 2021)
The Orang Asli group forms a minority community in Peninsular Malaysia, whose livelihood mostly depends on their land and the surrounding area. Dispute over customary land rights of Orang Asli has been continual in Malaysia although Malaysian Courts, in several cases, have upheld the Common Law rights of Orang Asli to their customary lands. This poses a challenge to some Orang Asli communities and State Governments. Based on focus group discussion, profiling survey, and library research methods, this paper analyses the land rights of Orang Asli in Peninsular Malaysia, by placing focus on Orang Asli in Kampung Parit Gong, Jelebu, Negeri Sembilan. The findings indicate that the Kampung Parit Gong Orang Asli community has been strictly adhering to the customs of â€˜adat perpatihâ€™ since yesteryears, and that they highly value the land, both through usage of land and by inheritance. Several important concerns were raised by the Orang Asli in Kampung Parit Gong, particularly on the security over their rights on the said customary land and the guarantee of their future generationsâ€%9